2004
DOI: 10.1111/j.1600-051x.2004.00529.x
|View full text |Cite
|
Sign up to set email alerts
|

High and low brushing force in relation to efficacy and gingival abrasion

Abstract: With the oscillating rotating power toothbrush (Braun/Oral-B D17) the use of high force (+/-3.5 N) is less efficacious as compared to a regular low force (+/-1.5 N) while the incidence of gingival abrasion sites was comparable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 17 publications
0
35
0
Order By: Relevance
“…Interestingly, energy transfer by non-contact brushing is inadequate to cause removal percentages over 60% (this study; see also [1]), which suggests that non-contact brushing can only make a biofilm thinner but is in its current technology unable to remove bacteria in the base, i.e., the initially adhering bacteria of a biofilm. Removal of bacteria in the base of a biofilm may therefore require direct contact with the bristles, which puts emphasis as well on the applied forces, which were chosen in this study on the basis of clinically reported forces for the different modes of brushing [9, 19, 38, 41]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, energy transfer by non-contact brushing is inadequate to cause removal percentages over 60% (this study; see also [1]), which suggests that non-contact brushing can only make a biofilm thinner but is in its current technology unable to remove bacteria in the base, i.e., the initially adhering bacteria of a biofilm. Removal of bacteria in the base of a biofilm may therefore require direct contact with the bristles, which puts emphasis as well on the applied forces, which were chosen in this study on the basis of clinically reported forces for the different modes of brushing [9, 19, 38, 41]. …”
Section: Discussionmentioning
confidence: 99%
“…The selected areas were brushed with a manual (Oral-B soft indicator Regular 40; Oral-B laboratories, Belmont, CA, USA), electric rotating (Oral-B Professional Care 7850 DLX; Braun GmbH, Kronberg, Germany), or sonic (Oral-B Sonic Complete; Braun GmbH, Kronberg, Germany) brush for 20 s, with the brush attached to a home-made moving tray, involving 20 strokes back and forth. Contact brushing was performed in a wetted state (i.e., with a thin film of water on the bottom plate but bristle tips not immersed) under a weight of 220 g for the manual, 150 g for the rotating, and 90 g for the sonic brush [9, 19, 41]. Subsequently, after re-mounting the bottom plate in the flow chamber, it was filled again with buffer and rinsed for 10 min, after which, ten images of the brushed areas were taken.…”
Section: Methodsmentioning
confidence: 99%
“…(11). The lesions were assessed as small (≤2 mm), medium (≥3 but ≤5 mm) and large (>5 mm) (15). Those between 2 and 3 mm were assigned a score of small or medium according to the nearest mm mark on the probe.…”
Section: Methodsmentioning
confidence: 99%
“…This solution has been used previously for detecting even minor areas of gingival abrasion, which would otherwise be largely undetectable, and this method has been suggested to be a sensitive tool for the identification of areas lacking epithelium (Van der Weijden et al 2004). This solution has been used previously for detecting even minor areas of gingival abrasion, which would otherwise be largely undetectable, and this method has been suggested to be a sensitive tool for the identification of areas lacking epithelium (Van der Weijden et al 2004).…”
Section: Surface Area Determinationmentioning
confidence: 99%